Translational research in amyotrophic lateral sclerosis (ALS) - Gitler, Aaron D. (Henry Stewart Talks, 2018)
The impact of recent genetic discoveries on ALS therapy options, Prevention vs treatment approaches, A personalized medicine approach to ALS treatment, Current open questions regarding the causes of ALS, Ongoing trials and future directions for ALS therapies, Translational research and academic-industry collaborations